The Importance of Service Elements in Retail Business - Verron Saputra; Aprihatiningrum Hidayati (Program Studi S3 Ilmu Manajemen, 2022)
This study aims to find out how the external and internal marketing strategic issues of Toko Delima, How is the internal and external analysis of Toko Delima and how is the recommendation of Toko Delima's marketing strategy for 2023. This type of research is a qualitative research with interview data collection methods conducted on Toko Delima owners, Toko Delima consumers and competitor’s store consumers, observation of competitors and documentation studies with secondary data related to Toko Delima. The data analysis method used in this research is by using qualitative analysis methods. The results of this study indicate that in the future Toko Delima will experience changes in STP and its marketing mix, namely in the aspects of price, place and promotion strategies. There is an addition to the service elements of Toko Delima, so that previously using 4P will become 7P. Toko Delima's marketing strategy recommendations for 2023 are promoting using social media namely Instagram, increasing store convenience, adding online sales channels, adding types of promotions and changing product pricing. The results of this study are expected to have a positive impact on the development of science and business in the field of management, especially how to design a marketing strategy